Green's function integral equation methods in nano-optics - Søndergaard, Thomas M. (CRC Press, 2019)
"The purpose of the book is to give a comprehensive introduction to using Green's function integral equation methods (GFIEMs) for solving scattering problems in nano-optics. The cases of interest from the area of nano-optics include scattering from metal nanoparticles, theoretical studies of the optics of nanostructured surfaces, and studies of scattering from objects placed on or near planar layered structures including optical waveguides. The book also covers different types of integral equation methods for 1D, 2D, and 3D scattering problems in nano-optics, how the integral equations can be discretized and solved numerically, and how this can be done efficiently"...